Distributed Temperature and Strain Measurements at a Cryogenic Plate‐Fin Heat Exchanger Test Rig. Issue 4 (3rd September 2021) - Fritsch, Philipp; Hoffmann, Rainer; Flüggen, Rainer; Woitalka, Alexander; Haider, Patrick; Rehfeldt, Sebastian; Klein, Harald
Abstract: A large cryogenic test rig was built to investigate dynamic operation of plate‐fin heat exchangers, which is needed for flexible operation of air separation units. This paper presents results from distributed temperature and strain measurements that were conducted during a dynamic test scenario. Results show that strong temperature gradients appear in all spatial directions of the heat exchangers, resulting in locally varying strains. It is shown that spatially dissolved, dynamic strain measurements are possible using optical fibers. Results from the test rig will help to properly instrument heat exchangers in research and in the field and provide important information for design and operation of plate‐fin heat exchangers in dynamic processes. Abstract : Distributed temperature and strain measurements were conducted at a cryogenic test rig for plate‐fin heat exchangers. Results show strong temperature gradients in all spatial directions and locally varying strains in the highly dynamic test scenario, influencing instrumentation, simulation, and design of heat exchangers for dynamic processes.